Projeto e construção de túnel de vento para ensaios de deposição de deriva associados à bioinseticida, adjuvantes e velocidades do vento - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
It is essential to carry out research that provides the correct supply of pesticides, in the necessaryquantity, in an economical way and with minimum contamination. In this context, the objectivewas to evaluate, in a wind tunnel, the position and drift of precipitation in different wind speedconditions. To this end, the present work was divided into three chapters called, respectively,“Sizing, construction and validation of an open circuit wind tunnel for the aerodynamic study ofagricultural spraying”; “Influence of wind intensity on spray drift simulated in a wind tunnel”and “Geostatistical modeling of the influence of adjuvants and wind speeds on drift deposition inbioinsecticide applications in a wind tunnel”. The experiments were extended at the StateUniversity of Goiás. An open circuit wind tunnel was designed and built, comprising an axialfan, stabilization chamber, nozzle, test section and diffuser. For validation, aerodynamicparameters were calculated and the analysis was performed using descriptive statistics. Researchon the influence of wind speed on drift deposits at different horizontal distances, carried out in awind tunnel, was conducted in a completely randomized design, in a 5 x 4 factorial scheme (airflow velocities x horizontal distances downwind). The study of the influence of adjuvants andwind speed intensity on spray deposition and drift in simulated applications with bioinsecticidebased on Bacillus thuringiensis was carried out in a wind tunnel, in a randomized design in a 5 x4 x 4 factorial scheme. The treatments consisted of five horizontal distances downwind (0.45m;0.75m; 1.05m; 1.35m and 1.65m), four wind speeds (1 m s-1, 2 m s- 1, 3 m s-1and 4 m s-1) andfour spray formulations (Water, Dipel®, Dipel® + Veget'Oil® Dipel® + Break Thru®). In bothchapters, drift deposition was collected using artificial targets positioned transverse to the windflow. The data were obtained by spectrophotometry and were subjected to analysis of variance(P<0.05) and when significant, the Tukey test and regression were applied, both at 5%probability. The software R and Sisvar were used for the analyses. For geostatistical analysis, theGS+ Version 7® software was used. The tunnel operates in good conditions, has laminar,incompressible flow and the wind flow showed low variation between points. Spray depositionwas greater at distances closer to the spraying site. Higher speeds made it possible to obtain largerdrift deposits. The use of Break Thru® adjuvant favored less loss due to drift in the upper andmiddle thirds. For the lower third, at a speed of 1 m s-1, the addition of Break Thru® adjuvantreduced drift, but at 4 m s-1the use of adjuvants did not promote a reduction in deposition inrelation to the mixture prepared with the insecticide. biological. The analyzed variable showed ahigh degree of spatial dependence for all treatments.
Design and construction of a wind tunnel for drift deposition tests associated with bioinseticide, adjuvants and wind speeds
Keywords: Tecnologia de aplicação; Bacillus thuringiensis; Bioinsumos; Velocidade do vento; Application technology; Bacillus thuringiensis; Bioinputs; Wind speed; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA